Gearing Up for Warmer Times: Transcriptomic Response of Spongia officinalis to Elevated Temperatures Reveals Recruited Mechanisms and Potential for Resilience - Koutsouveli, Vasiliki; Manousaki, Tereza; Riesgo, Ana; Lagnel, Jacques; Kollias, Spyros; Tsigenopoulos, Costas S.; Arvanitidis, Christos; Dounas, Costas; Magoulas, Antonios; Dailianis, Thanos (Frontiers in Marine Science, 2020)
The emblematic sponge Spongia officinalis is currently threatened by recurrent mortality incidents in its native habitats. Elevated temperature has been indicated as a major triggering factor, but the molecular mechanisms recruited for the organism’s response to thermal shifts are yet unknown. Here, we experimentally tested the effect of exposure to temperatures of varying intensity and span on its gene expression profile, replicating gradients encountered in the species’ native habitat. Analysis revealed major shifts in the organism’s transcriptomic profile induced by temperatures corresponding to the standard seasonal maximum, triggering processes related to signal transduction, inflammation and apoptotic pathway. Further elevation of temperature corresponding to local extremes activated further the immune response of the sponge along with protein ubiquitination. Following prolonged exposure, activation of endoplasmic reticulum stress related to accumulation of misfolded proteins and signs of resilience were observed. In the latter condition, categories such as cellular response to stress, wound repair, and diminution of pathological inflammation as also genes related to cell regeneration and cell growth were upregulated. Our results highlight the acknowledged sensitivity of S. officinalis to environmental shifts, providing an insight into the molecular mechanisms involved in the process. Furthermore, they suggest innate capacity for resilience at the current thermal extremes, implying a combination of factors and not temperature per se as the lethal agent. This sheds light on the mechanisms of pressure induced by the ongoing ocean warming trend to coastal sessile invertebrates.